PENGARUH PENGALAMAN PRAKTIK KERJA INDUSTRI DAN LINGKUNGAN KELUARGA TERHADAP INTENSI BERWIRAUSAHA SISWA SMK - Farida, Dewi; ., Siswandari; Hamidi, Nurhasan (FKIP Universitas Sebelas Maret, 2016)
ABSTRACTThe objectives of this research are to test (1) the effect of the industrial work practice experience on the studentsâ entrepreneurial intention; (2) the effect of the family environment on the studentsâ entrepreneurial intention; (3) and the simultaneous effect of the industrial work practice experience and the family environment on the studentsâ entrepreneurial intention. This research used the descriptive quantitative method with the ex post facto design. Its population was 107 of the school. The samples of research consisted of 84 and were deter-mined by using the simple random sampling technique. The data of research were collected through question-naire and analyzed by using the multiple regression technique of analysis. The results of research are as fol-lows (1) the industrial work practice experience has a positive and significant effect on the studentsâ entrepre-neurial intention as indicated by the value of tstat = 4.788 (at the significance level = 0.000); the family environ-ment has a positive and significant effect on the studentsâ entrepreneurial intention as signified by the value of tstat = 3.164 (at the significance level = 0.002); and (3) both the industrial work practice experience and the family environment have a simultaneously positive and significant effect on the studentsâ entrepreneurial inten-tion as shown by the value of Fstat = 71.804 (at the significance value = 0.000). The value of the adjusted R square is 0.630, which indicates that the independent variables simultaneously have an effective contribution of 63% on the entrepreneurial intention of the students.Keywords: Industrial work practice experience, family environment, entrepreneurial intentionABSTRAKPenelitian ini bertujuan untuk menguji (1) pengaruh pengalaman praktik kerja industri terhadap intensi berwirausaha siswa; (2) pengaruh lingkungan keluarga terhadap intensi berwirausaha siswa; (3) pengaruh pen-galaman praktik kerja industri dan lingkungan keluarga terhadap intensi berwirausaha siswa. Penelitian ini menggunakan metode deskriptif kuantitatif yang bersifat ex post facto. Populasi penelitian ini sebanyak 107 siswa dan sampel diambil sebanyak 84 siswa dengan teknik pengambilan simple random sampling. Data dik-umpulkan dengan kuesioner dan dianalisis menggunakan teknik regresi linier berganda. Hasil penelitian menunjukkan bahwa (1) pengalaman praktik kerja industri berpengaruh positif dan signifikan terhadap intensi berwirausaha siswa dengan t hitung sebesar 4,788 (sig.0,000); (2) lingkungan keluarga berpengaruh positif dan signifikan terhadap intensi berwirausaha siswa dengan t hitung 3,164 (sig.0,002); (3) pengalaman praktik kerja industri dan lingkungan keluarga secara simultan berpengaruh positif dan signifikan terhadap intensi ber-wirausaha siswa dengan nila F hitung 71,804 (sig.0,000). Adjusted R Square sebesar 0,630 menunjukkan bah-wa variabel independen secara bersama-sama memberikan sumbangan efektif sebesar 63% terhadap intensi berwirausaha siswa.Kata Kunci: Pengalaman Praktik Kerja Industri, Lingkungan Keluarga, Intensi Berwirausaha